Eksplorasi Pendekatan Dynamic Governance dalam Pengembangan Rumah Talenta Digital di Kabupaten Nganjuk - Dhiyaa Ulhaq Rohmatulloh; Adi Soesiantoro; Ghulam Maulana Ilman (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Nganjuk Regency Government shows a commitment to strengthen the capacity of MSME actors through activities such as digital training. However, the challenges of digital transformation demand a more adaptive strategy. The omah away program is present as a regional innovation in accelerating the digitalization of MSMEs, in line with the national vision towards the smart economy and digital transformation targets announced in the RPJMN. Based on the theory of Dynamic Governance with 3 variables such as Thinking Ahead, Thinking Again, and Thinking Across, this omah away program offers digital training, business legality facilitation, and marketing through digital platforms. This study highlights how the away house becomes an integrative model that not only provides technical training, but also builds a collaborative ecosystem between the government, business actors, the private sector, communities, education and society. Despite the impact on increasing the participation of digital MSMEs and reducing the unemployment rate, obstacles such as low business legality and online marketing effectiveness are still found. Therefore, critical reflection and cross-actor collaboration are key to the sustainability of the program. These findings strengthen the relevance of Dynamic Governance theory in the context of local-based digital transformation, as well as support efforts to achieve smart economy in areas with growing potential such as Nganjuk Regency.